The State of the AIIDE Conference in 2017 - Sturtevant, Nathan; Magerko, Brian (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
This abstract looks at the state of the Artificial Intelligence and Interactive Digital Entertainment Conference (AIIDE), describing some of the changes in the field and areas of focus for current work.